Synthesis and characterization of nickel complexes derived from dibenzo tetraaza[14] annulene for liquid crystal application / Nooraziah Mohd Lair - Nooraziah , Mohd Lair (2018)
A new series of macrocyclic dibenzotetraaza[14]annulenes (DBTAA) bearing 5-alkoxy-3,3-dimethylindole on meso positions and four aliphatic ether side chains on dibenzo structure, that consist of 6, 10, 12, 14 carbon length, respectively, were synthesized. The new compounds of macrocyclic DBTAA were synthesized through 2:2 condensation of 4,5-bis(alkoxy)benzene-1,2-diaminium chloride and 2-(diformylmethylidene)-5-(alkyloxy)-3,3-dimethylindole with glacial acetic acid as catalyst. The intermediate of 4,5-bis(alkoxy)benzene-1,2-diamininium chloride has been synthesized from alkylation on catechol using bromoalkyl (BrCnHn+1, n = 6,10,12,14) followed by nitration with concentrated nitric and sulphuric acid and finally reduction by Tin(II) chloride. As for 2-(diformylmethylidene)-5-(alkyloxy)-3,3-dimethylindole, the compound was synthesized from 4-methoxy phenylhydrazine via fischer synthesis followed by demethylation using boron tribromide, alkylation by alkylbromide, and lastly, Vilsmeier-Haack reaction was applied to afford the required compounds of diformyl. Reaction of nickel(II) acetate in glacial acetic acid on the synthesized macrocyclic DBTAA compounds has resulted in the target 1:1 type (ligand/metal ratio) of new DBTAA complexes. The new macrocyclic compounds and their nickel complex structures were characterized by ATR-FTIR, CHN, 1H and 13C NMR, UV-Vis, TGA and X-Ray crystallographic studies. In this study, as predicted the nickel complex possess a planar structure and four nitrogen atoms were coordinated to nickel atom in a square planar geometry which appeared as a weak d-d transition 500 to 505nm range in UV-Vis spectra. Liquid crystal properties of this new macrocyclic ligand and its complexes were studied under OPM and confirmed by DSC measurement. Macrocyclic ligands consisting of ether aliphatic chains of 12 and 14 carbon length were found to show liquid crystal properties. Nickel complexes with alkyl chains of 10 and 12 carbons also exhibited clearly the fan-shaped texture of discotic columnar liquid crystal properties under OPM. However, the rest of the macrocyclic ligands and complexes changed directly to crystal lattice upon cooling or heating. This observation was confirmed by DSC measurement, and the exact transition temperature with the enthalpy change (ΔH) can be identified on the observed peak at nearly the same temperature as when the texture appeared in OPM. The synthesized macrocyclic ligands and their nickel complexes which are having columnar liquid crystal properties could be suitable materials for organic semiconducting and optical storage.